Assessment of Hyoid Bone Position and its Correlation With Airway Dimensions in Different Sagittal Malocclusions Using Cone Beam Computed Tomography - Priya Singh; Supriya Nambiar; Asavari Desai; Nidhin Philip; Ravikiran Ongole (International Journal of Dentistry)
Conclusion: The hyoid bone is posteriorly positioned in Class II skeletal pattern. Oropharyngeal volume was least in Class II skeletal base individuals. In males, pharyngeal volume was larger than females, and the hyoid bone was placed inferiorly compared to females.